Polisi dan Polusi (Studi Kasus Kapasitas Paru Polisi Lalu Lintas Polres Kendari) (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2023)
Polantas (Traffic Police) is part of the Police that is needed by the community for security, especially traffic on the highway. The increase in the number of motorized vehicles has an impact other than traffic congestion can also trigger air pollution caused by motor vehicle emissions, this can have a negative impact on the lungs of traffic police. The purpose of this study was to obtain data on air quality in Kendari City and vital lung capacity of the Kendari Police Traffic Police. Measurement of lung capacity using a spirometry tool. The measurement of air quality uses the IMR 1600 tool. Measurements are carried out for at least 1 hour and then recorded in the form of a report. Parameters that can be detected by this tool: Carbon Monoxide (CO), Nitrogen Dioxide (NO2), and sulfur dioxide (SO2 ). The results showed that the vital capacity of the lungs of traffic police at the Kendari City Police consisted of three categories, namely normal, mild disturbances and moderate disturbances, while concentrations of sulfur dioxide (SO2), carbon monoxide (CO) and nitrogen dioxide (NO2) in the air, not exceeding the air quality standard. The results of the calculation of the correlation test show that there is no relationship between the air quality of both Sulfur Dioxide (SO2), Carbon monoxide (CO) and Nitrogen dioxide (NO2 ) with the vital quality of the lungs at the Traffic Police on duty at the Kendari Police.Keywords: Pollution, Lungs, Air Quality